Energy-Efficient Hybrid K-Means Algorithm for Clustered Wireless Sensor Networks - Aziz Mahboub; Mounir Arioua; El Mokhtar En-Naimi (International Journal of Electrical and Computer Engineering (IJECE), 2017)
Energy efficiency is the most critical challenge in wireless sensor network. The transmission energy is the most consuming task in sensor nodes, specifically in large distances. Clustered routing techniques are efficient approaches used to lower the transmission energy and maximize the network’s lifetime. In this paper, a hybrid clustered routing approach is proposed for energy optimization in WSN. This approach is based on K-Means clustering algorithm and LEACH protocol. The simulation results using MATLAB tool have shown that the proposed hybrid approach outperforms LEACH protocol and optimizes the nodes energy and the network lifetime.